História material e formação urbana: a dinâmica socioespacial de Limeira (SP) no século XIX - Manfredini, Eduardo Alberto (2010)
This study deals with the socio-spatial dynamics of the city of Limeira, seat of a municipality located in the eastern region of the state of São Paulo, seen primarily through the perspective of the reconstruction of material history registered in this urban nucleus during the 19th century. Research was carried out on the prior period, from 1799 when two Allotments were granted at the confluence of the Jaguari and Atibaia Rivers, the source of the Piracicaba River, and which would become, along with other land allotments, the municipal boundaries up until the final decade of that century. The study is thus based on the apprehension of the process of material evolution that marked the developing urbanization, perceived by the rediscovery of four variable factors which attended the establishment and development of the city: the formation and evolution of the transportation system, the installation and occupation of the urban street network, the location dimension of administrative edifications and the dynamic of urban equipment, both public and private. Research was made to identify how Limeira related to the national, state and regional contexts of that period, to describe the process of establishing towns near the geographical feature known as Morro Azul , or Blue Hill (where the present-day towns of Rio Claro, Araras and Piracicaba are also located), and, lastly, to understand significant social and historical facts related to physical expansion and to economic factors. The occupation of the land before the urban settlement was also dealt with, giving special attention in this process to the socio-spatial issues linked both to Allotments granted in the region and to the farms that were born out of those properties. Besides looking into pertinent scientific and technical literature available, direct documental sources were researched, found in collections of church documents in parishes and diocesan offices, in collections of public documents, in museums and libraries both public and private along with consultation and interpretation of historiographic bibliographies, as well as articles and laws, among others. The analyses which were elaborated show the materiality of space both as a result and as a basis for the evolution of social relationships and for the dominant class to stay in control, evidenced by forms of land appropriation and by the presence of a basis for the socio-spatial segregation found in the city in the next century, even though new configurations for the latter were adopted.